USING PICTURES TO IMPROVE STUDENT’S ABILITY TO UNDERSTAND ENGLISH DESCRIPTIVE TEXT - Nakuu, Cellina A.; Samola, Nurmin; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
Students should create descriptive text. Unfortunately, sometimes students get stuck in describing something. Because of these difficulties, an effort must be done to solve the problem. The solution is to teach by using media of pictures. The teacher used pictures to motivate students to write in the teaching and learning process. So, the students can express their thought, feelings, or ideas. The objectives of this study are: 1) To know the students’ ability in writing descriptive text before being taught by using media of picture. 2) To know the students’ ability in witting descriptive text after being taught by using media of pictures. 3) To know whether there is a significant difference between students’ ability in the descriptive text before and after being taught by using media of picture. This study used a quantitative approach with a pre-experimental design. The sample of this research is class VIII A, consisting of 26 students. Meanwhile, the instrument is a test used to conduct pre-test and post-test. The data collected through the pre-test and post-test were analyzed The result of the study showed that the mean score of the pre-test was 71,53 and the mean score of the post-test was 84,2, which is higher than the mean score of the pre-test. From the result, there is a significant difference in the student’s writing descriptive text before and after being taught by using pictures. Therefore, teaching descriptive using pictures effectively improves students’ ability in descriptive text.